Total robotic transhiatal excision for a large left-sided esophageal epiphrenic diverticulum: a case report - Sanjamjot Singh; Kaushal Singh Rathore; B Selvakumar; Vaibhav Kumar Varshney; Lokesh Agarwal; Subhash Soni; Peeyush Varshney; Sabir Hussain (Journal of Minimally Invasive Surgery)
Surgery for a symptomatic epiphrenic esophageal diverticulum (EED) typically involves a diverticulectomy with myotomy and partial fundoplication. A 54-year-old male patients presented with postprandial retrosternal pain and regurgitation. A contrast-enhanced computed tomography scan revealed an 8 × 6 × 7 cm left-sided EED. We planned the EED excision using the da Vinci Xi robot (Intuitive Surgical) from an abdominal transhiatal approach. The lower esophagus was looped, followed by the mobilization of the diverticulum and division of its neck using a robotic stapler. A 7-cm long esophagogastric myotomy was performed on the right side with a Toupet fundoplication. The total operative time was 240 minutes with a blood loss of 200 mL. An oral contrast study on postoperative day 1 showed no leak, and the patient was discharged the next day on an oral soft diet. The robotic transhiatal approach to treat EED is safe and may successfully overcome the difficulties of exposure and reach encountered in conventional laparoscopic surgery.